International controlled study of revascularization and outcomes following COVID‐positive mechanical thrombectomy. (26th July 2022) - Dmytriw, Adam A.; Ghozy, Sherief; Sweid, Ahmad; Piotin, Michel; Bekelis, Kimon; Sourour, Nader; Raz, Eytan; Vela‐Duarte, Daniel; Linfante, Italo; Dabus, Guilherme; Kole, Max; Martínez‐Galdámez, Mario; et al.
Abstract: Background and purpose: Previous studies suggest that mechanisms and outcomes in patients with COVID‐19‐associated stroke differ from those in patients with non‐COVID‐19‐associated strokes, but there is limited comparative evidence focusing on these populations. The aim of this study, therefore, was to determine if a significant association exists between COVID‐19 status with revascularization and functional outcomes following thrombectomy for large vessel occlusion (LVO), after adjustment for potential confounding factors. Methods: A cross‐sectional, international multicenter retrospective study was conducted in consecutively admitted COVID‐19 patients with concomitant acute LVO, compared to a control group without COVID‐19. Data collected included age, gender, comorbidities, clinical characteristics, details of the involved vessels, procedural technique, and various outcomes. A multivariable‐adjusted analysis was conducted. Results: In this cohort of 697 patients with acute LVO, 302 had COVID‐19 while 395 patients did not. There was a significant difference ( p  < 0.001) in the mean age (in years) and gender of patients, with younger patients and more males in the COVID‐19 group. In terms of favorable revascularization (modified Thrombolysis in Cerebral Infarction [mTICI] grade 3), COVID‐19 was associated with lower odds of complete revascularization (odds ratio 0.33, 95% confidence interval [CI] 0.23–0.48; p  < 0.001), which persisted on multivariable modeling with adjustment for other predictors (adjusted odds ratio 0.30, 95% CI 0.12–0.77; p  = 0.012). Moreover, endovascular complications, in‐hospital mortality, and length of hospital stay were significantly higher among COVID‐19 patients ( p  < 0.001). Conclusion: COVID‐19 was an independent predictor of incomplete revascularization and poor functional outcome in patients with stroke due to LVO. Furthermore, COVID‐19 patients with LVO were more often younger and had higher morbidity/mortality rates. Abstract : We conducted a cross‐sectional, international multicenter retrospective study of consecutively admitted COVID‐19 patients with concomitant acute LVO, compared to a control group without COVID‐19. Our results shows that COVID‐19 was an independent predictor of incomplete revascularization and poor functional outcome in patients with stroke due to LVO. In addition, COVID‐19 patients with LVO were more often younger and suffered higher morbidity/mortality rates.